ANTIDERMATOPHYTIC ACTIVITY OF STREPTOMYCES CACAOI SUBSP. CACAOI. M20 - T, Janaki (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Objective: This study is an approach to find the alternative drug for the dermatophytosis because some of the existing antibiotics cause toxicity and also found expensive. Methods: There were 25 actinomycetes isolated from the soil sample of the mangrove, Avicennia marina from Ariyankuppam backwater area, Puducherry. Among the 25 isolates, the most active isolate, M20 was selected initially based on its antifungal activity, and it was checked for antidermatophytic activity against three dermatophytes, Microsporum gypseum, Trichophyton mentagrophytes, and Epidermophyton floccosum by agar plug method, well diffusion method followed by food poisoning technique. Release of volatile compounds from the isolate M20 has also been tested. Ultraviolet (UV)-vis spectral analysis of partially purified yellow compound fraction was done. Results: The isolate M20 actively controlled the growth of dermatophytes by agar plug method in the primary screening, well diffusion method in the secondary screening. The isolate was identified as Streptomyces cacaoi sub sp. cacaoi by 16sRNA sequencing analysis. The 10% (10 ml) culture filtrate of the isolate M20 was found to control the radial growth of these three dermatophytic fungi by food poisoning technique. Volatile compounds of the isolate M20 affected the mycelial growth of M. gypseum tremendously. Complete arrest of growth of M. gypseum was noticed with the combination of both volatile and non-volatile antibiotic compound of the isolate M20. The partially purified compound fraction (yellow) (0.5 mg/6 mm disc) inhibited the growth of M. gypseum (12 mm), and it was compared with the standard antibiotic clotrimazole (0.5 mg/6 mm disc), whose inhibition on M. gypseum was only 6 mm. UV-vis spectral analysis revealed the compound belonged to nucleoside antibiotics. Conclusion: It is evident that the mangrove actinomycetes are potential for preparing biomedicines for human welfare.